2016
DOI: 10.1097/md.0000000000004804
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, practices, and traditional beliefs related to neonatal jaundice among Egyptian mothers

Abstract: Neonatal jaundice (NNJ) is one of the most common neonatal disorders worldwide. It is still a main cause of avoidable brain damage, physical and mental impairment, and probable death in newborns.We aimed to assess perceptions, practices, and traditional beliefs among Egyptian mothers toward NNJ that may contribute to delayed presentation and inappropriate management of hyperbilirubinemia.This descriptive, cross-sectional study was conducted from January to May 2015. We interviewed 400 Egyptian mothers who gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
6
20
5
Order By: Relevance
“…Many of them still considered home remedies and sunlight exposure as initial treatment options. Similar practices are observed in studies from underdeveloped countries in Asia and Africa (14) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Many of them still considered home remedies and sunlight exposure as initial treatment options. Similar practices are observed in studies from underdeveloped countries in Asia and Africa (14) .…”
Section: Discussionsupporting
confidence: 84%
“…Moawad et al (14) studied the perceptions, practices, and traditional beliefs related to neonatal jaundice among Egyptian mothers. In this study a total of 400 mothers participated and revealed moderate knowledge and attitude scores of Egyptian mothers in most domains with a mean of 6.6 and 20.6, respectively, although the majority of them were illiterate or had low educational attainment and lived in rural areas (89.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate maternal knowledge, early perception, and care seeking behaviour are fundamental components of effective management of NNJ 15 . In this study, only 22% of mothers had an adequate level of knowledge about NNJ whereas a study conducted in Egypt showed that 52.3% of participants had adequate knowledge about NNJ 16 . The majority (87%) of respondents knew that NNJ was yellowness of the eyes and 79% of the mothers correctly indicated the eyes as the part of the body where jaundice is first noticed.…”
Section: Discussioncontrasting
confidence: 76%
“…14 In this study, only 22% mothers had adequate level of knowledge about NNJ whereas a study conducted in Egypt shows that 52.3% of participants had adequate knowledge about NNJ. 15 The majority (87%) of respondents knew that NNJ was yellowness of the eyes and 79% of the mothers correctly indicated the eyes as the part of the body where jaundice is first noticed. This finding supported previous studies.…”
Section: Discussionmentioning
confidence: 97%